The Ottoman world : a cultural history reader, 1450-1700 - Karateke, Hakan T.; Anetshofer, Helga (Oakland, California : University of California Press, 2021)
"The Ottoman lands, which comprised a geography extending from modern Hungary to the Arabian peninsula, were home to a vast population with a rich variety of cultures. The Ottoman World is the first primary source reader designed to reflect a wide and diverse set of voices across Ottoman society and bring them into the classroom. Written in many languages-not only Ottoman Turkish, but also Arabic, Armenian, Greek, Hebrew, Italian, and Persian-these texts span the extent of the early modern Ottoman empire, from the 1450s to 1700. Instructors are supplied with narratives conveying the lived experiences of individuals through texts that highlight human variety and accelerate a trend away from the 'state-centric' approach to Ottoman history. In addition, samples from court registers, legends, biographical accounts, hagiographies, short stories, witty anecdotes, jokes, and lampoons provide us with exciting glimpses into popular mindsets in Ottoman society. By reflecting new directions in the scholarship with its innovative choice of texts, this sourcebook will provide a vital resource for teachers and students"--
Frontmatter -- CONTENTS -- ILLUSTRATIONS -- ACKNOWLEDGMENTS -- PREFACE -- 1 Letters of an Insecure Scholar, 1553 -- 2 Adversities at Sea: From Basra to Gujarat, 1554 -- 3 Memoirs of an Ottoman Captive in Malta, 1597-98 -- 4 The Excommunication of a Greek Orthodox Priest, ca. 1642 -- 5 Dream Letters of a Sufi Woman in Skopje, 1640s -- 6 Diary of a Sufi Sheikh in Plague-Ridden Istanbul, 1661 -- 7 Ramblings of an Eccentric Sufi Exiled on Limnos, ca. Early 1680s -- 8 Adventures of an Ottoman Officer in Captivity, 1690-99 -- 9 The Trial of a Heretic, 1527 -- 10 The Life and Works of Two Mediocre Poets -- 11 The Extraordinary Life Story of a Scholar -- 12 On Servants and Slaves -- 13 Children and Youth -- 14 Women at Courts of Law -- 15 Prostitutes and Pimps -- 16 On Nocturnal Activities -- 17 Impostors, Frauds, and Spies -- 18 The Madmen of Istanbul -- 19 Fetvas on Non-Muslims -- 20 Conversion Among Ottoman Jews -- 21 Marriage and Divorce Among Ottoman Jews -- 22 News from Istanbul at the Turn of the Seventeenth Century -- 23 Propagating the Faith in Constantinople -- 24 An Armenian Chronicle of Crimea -- 25 On Revenants and Ghosts -- 26 Miracles of an Anatolian Sufi Saint -- 27 A Dispute Concerning Sufi Tombs, 1619 -- 28 Preserving Public Health -- 29 Traditional Medicine for Everyday Ailments -- 30 Snake Medicine and Snake Charming in Cairo -- 31 On Smoking Tobacco -- 32 Divining Past, Present, and Future in the Sand -- 33 Reading Character by Appearance -- 34 Religious Guidance for Hunters -- 35 Cultivating the Land -- 36 Wonders of Art and Nature -- 37 On the Natural Advantages of Edirne -- 38 The Legend of the Construction of Constantinople -- 39 On the Construction of the Pyramids, ca. 1545 -- 40 An Ode to Istanbul -- 41 Passion and Murder on the Bosphorus -- 42 Stories of Guilt and Repentance -- 43 The Wiles of Women -- 44 Social Criticism and Invective in Poetry -- 45 Shrewd Witticisms by a Master Poet -- 46 Subversive Jokes Featuring a Folk Hero -- INDEX
Includes index.
Description based on print version record and CIP data provided by publisher.
In English.
eBooks on EBSCOhost
Keywords: Turkey -- History -- Ottoman Empire, 1288-1918 -- Sources; Turkey -- History -- Ottoman Empire, 1288-1918 -- Early works to 1800.; Empire ottoman -- Histoire -- Sources; Empire ottoman -- Histoire -- Ouvrages avant 1800.; HISTORY / Middle East / Turkey & Ottoman Empire; Turkey; 1288-1918; Early works; History; Sources